2017
DOI: 10.1016/j.renene.2017.02.053
|View full text |Cite
|
Sign up to set email alerts
|

Influence of non-uniform heat flux distributions on the secondary flow, convective heat transfer and friction factors for a parabolic trough solar collector type absorber tube

Abstract: Highlights •Thermal analysis of a parabolic trough collector (PTC) for laminar flow liquid water heating. •Buoyancy effects are less significant in flat plate solar water heaters but significantly enhance PTC efficiency. •With buoyancy effects, average and axial local internal heat transfer coefficients are far greater than when neglected. •Internal heat transfer coefficients increased with heat flux intensity and absorber tube inlet fluid temperature. •Friction factors decreased with an increase in the inlet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…7 highlight a decrease in temperature gradients as the Reynolds number increases. Okafor et al [ 45 ] observed a similar trend in temperature gradient for corrugated conduits with increasing Reynolds numbers and stated that this decrease in temperature gradient contributes to an enhancement in the heat transfer rate.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…7 highlight a decrease in temperature gradients as the Reynolds number increases. Okafor et al [ 45 ] observed a similar trend in temperature gradient for corrugated conduits with increasing Reynolds numbers and stated that this decrease in temperature gradient contributes to an enhancement in the heat transfer rate.…”
Section: Resultsmentioning
confidence: 83%
“…Moreover, Xiangyang et al [ 22 ] conducted an experiment on a circular tube with molten salt subjected to NUHF conditions and identified that the Nu of the molten salt flow enhanced with Re . Besides that, Okafor et al [ 23 ] numerically investigated an absorber tube shaped like parabolic troughs for solar collectors under non-uniform heating conditions with Re ranging from 130 to 2200 and discovered that the heat flux which was distributed non-uniformly led to a significant increase in both overall and local heat transfer coefficients because of the buoyancy-driven secondary flow. Furthermore, Huang et al [ 24 ] investigated mixed heat transfer and flow behavior under NUHF inside a horizontal plain tube for turbulent flow.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was found that an inverse relation exists between the HTF velocity and the temperature gradient of the absorber metal. However, an alternative numerical approach to represent the nonuniform heat flux was presented by Okafor et al using the sine equation expression in terms of concentrated base‐level heat flux under laminar flow regime. Different Re numbers, different receiver diameters, and different fluid inlet temperatures have been considered to study their effect on the secondary flow.…”
Section: Literature Review Of Ptcsmentioning
confidence: 99%
“…The heat transfer coefficient (HTC) values and friction factors mostly increased with the NUHF [21], and secondary flow was enhanced by increases in the Grashof number and decreases in the Reynolds number [21]. Okafor, et al [22] presented a numerical model for mixed convection laminar flow and showed buoyancy-induced secondary flow to significantly enhanced the HTC, increasing with heat flux intensity and angle span.…”
Section: Introductionmentioning
confidence: 99%